2011
DOI: 10.1038/hdy.2011.120
|View full text |Cite
|
Sign up to set email alerts
|

Exploring neutral and adaptive processes in expanding populations of gilthead sea bream, Sparus aurata L., in the North-East Atlantic

Abstract: Recent studies in empirical population genetics have highlighted the importance of taking into account both neutral and adaptive genetic variation in characterizing microevolutionary dynamics. Here, we explore the genetic population structure and the footprints of selection in four populations of the warm-temperate coastal fish, the gilthead sea bream (Sparus aurata), whose recent northward expansion has been linked to climate change. Samples were collected at four Atlantic locations, including Spain, Portugal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 102 publications
2
40
0
1
Order By: Relevance
“…The aim of this study was to re-investigate patterns of genetic differentiation among sea bream populations collected in coastal lagoons of the Gulf of Lions using a larger array of microsatellite markers than in previous studies in this species (Alarcón et al 2004, De Innocentiis et al 2004, Chaoui et al 2009; but see Coscia et al 2012). A particular focus was made on microsatellite markers located close to 2 candidate genes, GH and Prl, that are functionally related to growth and osmoregulatory capacities in fish (Streelman & Kocher 2002, Almuly et al 2008, Quéré et al 2010) and have been previously showed to be involved in habitat-based genetic differentiation in sea bream (Chaoui et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to re-investigate patterns of genetic differentiation among sea bream populations collected in coastal lagoons of the Gulf of Lions using a larger array of microsatellite markers than in previous studies in this species (Alarcón et al 2004, De Innocentiis et al 2004, Chaoui et al 2009; but see Coscia et al 2012). A particular focus was made on microsatellite markers located close to 2 candidate genes, GH and Prl, that are functionally related to growth and osmoregulatory capacities in fish (Streelman & Kocher 2002, Almuly et al 2008, Quéré et al 2010) and have been previously showed to be involved in habitat-based genetic differentiation in sea bream (Chaoui et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Protocols for PCR amplification and genotyping at these 2 loci are reported in Chaoui et al (2009). The remaining 21 microsatellite loci were developed by Franch et al (2006) and Coscia et al (2012) (Table S1) and were considered as putatively neutral. These loci were grouped in 2 multi plexes of 10 and 11 loci for GH and Prl genes, respectively.…”
Section: Microsatellite Genotypingmentioning
confidence: 99%
“…In the last decade, a significant increase in wild gilthead seabream populations has been documented and linked to climate change in some coastal zones such as the northeast Atlantic (Coscia et al 2011). In other Mediterranean locations such as Messolonghi lagoon in Greece, this phenomenon was related to the farming of large mature specimens in commercial aquaculture farms which spawned in the sea cages (Dimitriou et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We assumed a widely accepted rate μ = 11% per site per million year for the Sparid mtDNA control region (Bargelloni et al, 2003;Sala-Bozano et al, 2009;Coscia et al, 2012), equal to 0.055 substitutions per site per million years. The age at maximum egg production was estimated with L inf = 47 cm for C. puniceus and L inf = 75 cm for C. nufar (where L inf , a parameter of the von Bertalanffy growth equation, is defined as the length that an individual would reach if it grew indefinitely).…”
Section: Statistical Analysesmentioning
confidence: 99%